(3YRjRJj JGQGs (3QSGFd eKjQI ddhfSs - (3cQje, ZGOIs ((3GdbGgQIs (3GdQhGbs, 2023)
(3YRjRJj JGQG Hbde ZGOI cQje (B... (3ce TNkUG ogfG jYGfj ef GdhMOI? QHeG dOjg Yeld EHOGYklj efaQlO HPGJg, Ch jfJej Edi HjFpI Yed YOGFjI dG JeSM Ydi bdHg HbWQGpJ GdhfS, Ch jYjT eY TQjmc jboa eYg Ydi fUpd Spqcjpf Gdnedpd, Ch dG jedoc TQjnc MjGmI ef GdCSGpS(B. (3jYjoT GdCWaGod MjGkI SYjOkI dCfgG SgdI, Ef de jpLOhG ajgG CUObGA JcnqdehG eY GdqOHGOjH, hEf CdbhngG ef GdfGaPpI UHGkMG GNJQYhG UOjkbG hgekqjG ddJMoqOK Edjg aj GdHGfjh cd eSGA(B. (3bnqQQJ GSJYGQnI acQI GdCWaGd Yf nNrdb GdhfS, hSCcoJoH Edi UOjbmI NjGdjmI JSocof chcnH GdpeQjN, hSCefMgG GSe (S0(3JGQG(S1(B. (3hdCf WQjnb GdYhOI Ydi SGYj GdHQjO TGlqb; agj QSGFd ef WQma hGMO, SJchf oeKjQI LkqOG ddhnfS dcpqd ef jQjO ogOfkI ef GdHTQ(B. (3CJefi dc QMdkI eeJYkI, HQLGA QHW GdMRGe Ydi bdHc LjkOGs
Keywords: (3QSGFds; (3ebGdGJs